P253 Characteristics of patients with Crohn's disease diagnosed in the emergency department: Experience in a single tertiary hospital. (16th January 2018) - Lee, S W; Kim, S K; Kim, E S; Lee, H S; Kwon, Y H; Nam, S Y; You, N; Lee, J S; Jin, S
Abstract: Background: Crohn's disease(CD) is characterised by chronic inflammation throughout the bowel. Some patients with CD may be diagnosed in the emergency department. However, characteristics of these patients are unknown. The aim of this study was to determine the clinical characteristics and outcomes of the patients who were diagnosed with CD in the emergency department compared with those who were diagnosed in the outpatient clinic. Methods: From 2011 to 2016, medical records were reviewed for patients diagnosed with CD at tertiary referral hospital. Patients were divided into two groups those diagnosed in the emergency department (ED) and in the outpatient clinic (OPD). We investigated demographic and clinical characteristics such as disease behaviour and location according to the Montreal Classification. We also compared clinical outcomes including the use of biologics and bowel resection surgery during follow-up period using Kaplan–Meier (KM) analysis. Results: Overall, 168 CD patients were included in the study (male 70.8%, mean age 30.7 ± 14.6, 45 ER, 123 OPD). There was no significant difference in diagnosis age, sex and follow-up period between groups. The rate of penetrating of penetrating type was significantly higher in ED than OPD (37.8% vs. 9.8%, p-value<0.001). CD location did not show any significant difference in both groups. KM analysis showed that time from diagnosis to surgical resection in ED was significantly shorter than OPD during the 36-month follow-up (log rank test, p = 0.045). However, this significance was not observed in the longer follow-up (72 months). There was no difference in the use of biologics between the groups. Conclusions: This study showed that CD patients diagnosed in the ED had more complicated disease behaviour compared with those who diagnosed in the OPD. This characteristic of ED appeared to be associated the high risk of early bowel resection surgery compared with OPD.